Influences of CNT dispersion and pore characteristics on the electrical performance of cementitious composites. (15th March 2017) - Kim, G.M.; Yang, B.J.; Cho, K.J.; Kim, E.M.; Lee, H.K.
Abstract: In the present study, cementitious composite incorporating a carbon nanotube (CNT) with highly improved electrical conductivity comparable to that of a semiconductor is developed and investigated. The CNT and pore characteristics within a cementitious matrix are considered as the most influential factors which determine the overall performance of the material, and these factors are artificially controlled by incorporating silica fume and a superplasticizer. Additionally, a micromechanics-based model is proposed to predict the electrical performance and percolation threshold of the composites. A parametric study based on the developed model is conducted, and the influences of the constituent properties on the overall electrical characteristics of composites are discussed. The effectiveness of the proposed hypothesis is demonstrated by comparing it to the experimental results in the present study and from the previous work.